THE EFFECT OF PREVENTIVE COUNSELING ON REDUCING BULLYING CASES IN ELEMENTARY SCHOOL - Titik Nuryanti; M. Yunus Sudirman; Ahmad Yani; Delvy Mardvin Siokain; Agustin Andhika Putri (International Journal of Educatio Elementaria and Psychologia, 2025)
Bullying in elementary schools is a pervasive issue that significantly impacts students’ emotional well-being, social relationships, and academic performance. Preventive counseling has emerged as a proactive approach to address bullying by equipping students with emotional resilience, empathy, and conflict resolution skills. This study investigates the effectiveness of preventive counseling in reducing bullying incidents among elementary school students. The research aims to evaluate whether structured counseling programs can decrease the frequency and severity of bullying cases and improve peer interactions within the school environment. A quasi-experimental design was utilized, involving pre-test and post-test assessments with a control group. The sample consisted of 80 elementary school students, divided equally into experimental and control groups. Data were collected through bullying incident reports, peer relationship surveys, and teacher observations. These results highlight the effectiveness of preventive counseling in fostering a safer and more supportive school climate. The study concludes that preventive counseling is a vital intervention to address bullying and recommends its broader implementation in elementary education.